1992
DOI: 10.1007/bf00226005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic renal effects in three studies of men and women occupationally exposed to cadmium

Abstract: We measured sensitive indicators of renal damage in three different populations occupationally exposed to cadmium, and examined the degree of variation in damage and the relative sensitivity of different types of indicators. The three studies included (1) men exposed in a cadmium recovery plant, (2) men exposed in a nickel/cadmium battery plant, and (3) women exposed in the latter plant. The indicators of renal damage were urinary proteins in three categories: (1) the high molecular weight enzymes alanine amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…Results from previous studies of high occupational cadmium exposures have suggested that urinary albumin may be a sensitive indicator of cadmium-induced renal effects (7). Cadmium levels in the high-exposure groups from these studies ranged from 6 µg to 16 µg cadmium/g creatinine (7), well above the levels observed in this study's environmentally exposed population.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…Results from previous studies of high occupational cadmium exposures have suggested that urinary albumin may be a sensitive indicator of cadmium-induced renal effects (7). Cadmium levels in the high-exposure groups from these studies ranged from 6 µg to 16 µg cadmium/g creatinine (7), well above the levels observed in this study's environmentally exposed population.…”
Section: Discussioncontrasting
confidence: 43%
“…An association between AAP and urinary cadmium was previously observed in studies of individuals with high occupational exposures (7,11), and NAG has been used as a marker of cadmium nephrotoxicity in several occupational and environmental studies (7,(10)(11)(12)33,34).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations